On Weakly (μ, λ)-Open Functions - Roy, B. (Ukrains’kyi Matematychnyi Zhurnal, 2014)
We study some characterizations and properties of almost (μ, λ)-open functions. Some conditions are presented under which an almost (μ, λ)-open function is equivalent to a (μ, λ)-open function.